Companies and the Constitutional ‘Right to Life’: A Critical Analysis of the Companies Act 71 of 2008 - Phiri, Siphethile (Richtmann Publishing, 2021)
Corporate law is founded on the fictitious principle of the separate legal personality of a company. This principle entails that a company is a juristic person, separate and distinct from any persons involved with the company. Because of their juristic nature, companies can acquire rights and incur liabilities in their own capacity. This corporate-law principle is rooted in section 8(4) of the Constitution of the Republic of South Africa, 1996 (hereafter the Constitution) which expressly provides the Bill of Rights applies to juristic persons subject to the stated considerations. The fact that companies as juristic persons, similar to natural persons, are entitled to the rights and freedoms contained in the Bill of Rights reveals that the Constitution recognises companies as ‘persons’. In this light, the article investigates how the Companies Act 71 of 2008 (hereafter the Companies Act) has embraced the constitutional right to life of companies as juristic persons as provided for in section 11 of the Constitution. To achieve this aim, the author applies the doctrinal legal research methodology – a legal research model which entails an examination of so-called ‘black-latter law’ with the Companies Act being the principal instrument. The results show that, although companies to do not enjoy the right to life in the same manner as natural persons, the literature examined reveals that the Companies Act recognises company’s constitutional right to ‘life’. In many instances, the right to continued existence of companies is promoted in various ways, including the introduction of the novel concept of business rescue by the Companies Act as a way of promoting the right to ‘life’ of companies. Received: 20 August 2021 / Accepted: 7 October 2021 / Published: 5 November 2021